Introduction: Turnaround and let-down: making sense of Brazil and Africa after the surge - Alencastro, M.; Seabra, P. (Brazil-Africa Relations in the 21st Century: From surge to downturn and beyond, 2021)
By improving political connections under a common South-South aegis, promoting new trade opportunities and expanding the disbursement of significant amounts of development cooperation, Brazil quickly secured a foothold of its own in Africa between 2003 and 2014. However, in the face of a political meltdown and of controversial judicial investigations back home, Brazil’s inversions in Africa have since then essentially collapsed. This abrupt turnaround calls for a more critical exegesis of the years of expansion. What were the main successes and failures of Brazil’s overall strategy towards Africa? And what does the dramatic change of events, with Brazil moving from a pivotal player to an almost invisible one in merely half a decade, tell us about the possibility of a new pick-up of interest for Africa? This introduction to the edited volume takes stock of the main trends in previous literature over the character and content of Brazil’s foreign policy towards the continent and sets the ground for the following chapters.